Tantangan Dan Peluang Pasar Modal Indonesia Di Era Globalisasi - Muhammad Zainul Azkiya; Rani Hersanda; Septiana Aulia Putri (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to examine the challenges and opportunities of Indonesia’s capital market in the context of economic globalization. The research employs a qualitative method through literature review, utilizing sources from academic journals, official financial institution reports, and credible media articles. The findings reveal that Indonesia’s capital market faces several challenges, including volatility driven by global dynamics, foreign investor dominance, low financial literacy, and limitations in regulatory and infrastructure aspects. Nevertheless, globalization also presents vast opportunities through access to international capital, digital technology advancements, and pro-investment government regulations. Digital transformation, the rise of young retail investors, and the development of sustainable investment instruments such as green bonds are positive indicators of the market’s progressive direction. A coordinated strategy among the government, market authorities, and industry players is essential to optimize these potentials and build an inclusive, efficient, and resilient investment ecosystem amid increasing global competition.